CROSS-CULTURAL PSYCHOLOGY: STILL STRUGGLING WITH ITS ENCOUNTERS OF THE OTHER - Skovdal, Morten (PINS-Psychology in Society, 2025)
Laungani, P M (2007) Understanding Cross-Cultural Psychology: Eastern and Western Perspectives. London: Sage Publications. ISBN-13: 978-0761971542. Pages xvi + 280. Cross-cultural psychology has been at the forefront in demonstrating that psychological phenomena differ according to their cultural setting and it has identified various cultural factors that can explain these differences (Ratner and Hui, 2003). One of the first to draw a link between psychology and the environment in which one lives was Vygotsky (1978). In his book Mind and society, Vygotsky highlights that the mind and society cannot be understood in isolation. Human beings are the only animal who uses tools to alter their own inner world as well as the world around them. It is the society that provides the individual with the tools to shape the private processes of mind.